Analysis of Employee Voice Mediation towards Industrial Relations Climate: An Empirical Study on BSM Banda Aceh - Harmen, Hamdi; Hanif, Muhammad; Ariyanto, Agus (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to analyze the effect of ethical leadership and organizational commitment towards the industrial relations climate mediated by employee voice. The population in this study was the employees of BSM (Bank Syariah Mandiri) Banda Aceh and the sample used was 83 people with a simple random sampling technique. This research data collection used a questionnaire. The data analysis technique used multiple linear regression analysis to examine the direct effect between variables and the Sobel Test analysis to test the indirect effect (mediation). The results found that there is a significant effect of ethical leadership towards the industrial relations climate. There is an effect of organizational commitment towards employee voice. There is an effect of employee voice towards the industrial relations climate. There is no effect of ethical leadership towards employee voice. There is no mediating effect of employee voice on the effect of ethical leadership towards the industrial relations climate. There is no mediating effect of employee voice on organizational commitment variable towards industrial relations climate for employees of BSM Banda Aceh